Meeting the Energy Needs of the Urban Poor : Lessons from Electrification Practitioners - Rojas, Juan Manuel; Lallement, Dominique (World Bank, Washington, DC, 2014)
The present report was prepared on the basis of the findings of an international workshop held from September 12-14, 2005, in Salvador da Bahia, and was attended by delegations of three to five practitioners from 12 cities in Latin America, Africa and Asia. It had two main objectives: (a) to share experiences on innovative solutions to provide electricity services in poor peri-urban and urban areas; and (b) to develop a body of knowledge to be disseminated and used by a wide array of practitioners involved in the provision of energy services in those areas. One of the most important conclusions of the Bahia workshop was that excluding part of the population from access to energy on account of their poverty, marginalization and the informality of the settlements has enormous long-term social, economic and financial costs. The root cause of the contemporary difficulty in providing electricity and other infrastructure services through public or private utilities is decades of such social exclusion, poverty and marginalization which have led to total distrust between formal structures and consumers, and to the rise of illegal and costly electricity distribution systems, often managed by private illegal entrepreneurs. Do current regulatory systems support slum electrification? At the institutional level, it was confirmed that in the majority of the countries participating in the workshop, except for Brazil, electrification programs for poor peri-urban and urban areas are being deployed with a lack of appropriate regulatory frameworks to support these efforts. The regulatory frameworks which have been developed for the general model of public-private partnership do not meet the need of distribution companies working in predominantly poor areas. In particular, they do not reflect the need for innovative technical characteristics and the informal sector relationships which characterize poor urban and peri-urban areas, nor are there regulatory mechanisms for risk-sharing or resolving disputes, for example, when the infrastructure is damaged. It would be important, therefore, to adapt regulatory frameworks for the various business models used to extend the grids to slums. Currently, utilities are left to their own devices to find out practical solutions. This is an area which was identified as needing more analytical work.